9 - Les universitaires ivoiriens et Internet - Bahi, Aghi (Africa Development, 2006)
By promoting a ‘knowledge society’, the development of ICT has had critical consequences on Ivoirian universities, thus putting them in an even more severe competition with other university systems. The technological gap is so wide that it seems quite impossible to take up the challenge of filling it. However, ICTs have appeared in people’s daily life, changing their universe and being used to produce and disseminate knowledge. This study has been carried out on a sample of teacher-researchers at the University of Cocody, and is based on individual interviews. The analysis is about the difficulties of Ivoirian scholars to use the Internet, and also deals with an issue which is fundamental in the life of a researcher, which is access to and production of scientific texts. The author is trying to understand the individual rationale behind the use of ICTs, in the context of scholar knowledge production.